2000
DOI: 10.1080/028418600750013465
|View full text |Cite
|
Sign up to set email alerts
|

Hypopharyngeal Squamous Cell Carcinoma: Treatment Results in 138 Consecutively Admitted Patients

Abstract: The aim of this study was to evaluate the results of the initial and salvage treatment for hypopharyngeal carcinoma. The study was conducted in 1963 to 1991 and included 138 patients (38 females (28%) and 100 males (73%)). Most of the tumours originated in the piriform sinus (86%). Tumour stage distribution was T1: 20%, T2: 27%, T3: 37% and T4: 17% and nodal stage distribution was N0: 45%, N1: 25%, N2: 10%, and N3: 20%. Primary treatment was delivered with curative intent in 124 out of 138 cases (90%). Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…In the retrospective analysis of Elias et al [32] on treatment results of carcinoma of the pyriform sinus, 32.0% of patient population developed distant metastases. The frequency of DM of 46.7% as first site of failure in our study was ten fold higher compared to the results reported by Johansen et al [2]. Although it is generally considered that locoregional control of head and neck cancer represents an important factor for development of distant metastases, we did not observe any distant metastases development preceded by occurrence of locoregional recurrence.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In the retrospective analysis of Elias et al [32] on treatment results of carcinoma of the pyriform sinus, 32.0% of patient population developed distant metastases. The frequency of DM of 46.7% as first site of failure in our study was ten fold higher compared to the results reported by Johansen et al [2]. Although it is generally considered that locoregional control of head and neck cancer represents an important factor for development of distant metastases, we did not observe any distant metastases development preceded by occurrence of locoregional recurrence.…”
Section: Discussioncontrasting
confidence: 76%
“…In the study of Yoon et al [30], the 3-year locoregional control for the group treated with CRCT was 52.0%. Johansen et al [2] in their study of treatment results in 138 patients with hypopharyngeal carcinoma reported low rates of locoregional control at 5 years (25.0%). The 2-year DMFS rate in our study was 64.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, pharyngeal cancer was usually detected at advanced stages, and its prognosis has been poor [ 8 ]. Surgical resection for advanced pharyngeal cancer is necessary, which could cause swallowing disorders, dysgeusia defect, speech problem, and serious cosmetic deformities of the neck [ 8 , 9 ]. ESD was first developed in the gastrointestinal tract and has been widely used because of its less invasion and good clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding different therapy concepts for stage I and II hypopharyngeal carcinomas, the 5-year survival rate averages between 52% and 77% for radiotherapy (with or without concomitant chemotherapy) [201], [202], [203], [204], between 56% and 77% for supraglottic or supracricoid hemilaryngopharyngectomy (with or without induction chemotherapy, neck dissection or postoperative radiotherapy) [205], [206], [207], [208], and between 70% and 73% for transoral laser microsurgery (with or without neck dissection or postoperative radiotherapy) [209], [210], [211]. The 5-year survival rates for stage III and IV hypopharyngeal carcinomas are 19%–37% for radiotherapy (with or without concomitant chemotherapy) [212], [213], [214], [215], and 47%–59% for transoral laser microsurgery (with or without neck dissection or postoperative radiotherapy) [209], [210]. Induction chemotherapy followed by radiotherapy achieved a 5-year survival rate of 38% in stage III and IV hypopharyngeal carcinomas [216].…”
Section: Carcinomas Of the Hypopharynxmentioning
confidence: 99%